Nudge in Signboard Tax Collection: An Experimental Behavioral Approach: สติกเกอร์ป้าย: มาตรการสะกิดการชำระภาษีป้ายด้วยแนวทางเชิงพฤติกรรมศาสตร์ - Krueathep, Weerasak; Wattatham, Sadanon; Komut, Wasin; Jaikampan, Kraiwuth (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ บทความนี้นำเสนอแนวคิดการสะกิด (Nudge) โดยสติกเกอร์ป้ายเพื่อเพิ่มผลสำเร็จของการจัดเก็บภาษีป้าย และนำไปทดลองใช้ในพื้นที่ อปท. จำนวน 4 แห่งในช่วงฤดูกาลจัดเก็บภาษีป้ายปี พ.ศ. 2563 ซึ่งได้เปรียบเทียบผลการทดลองกับกลุ่มควบคุมจำนวน 1 แห่ง และใช้วิธีประเมินผลเปรียบเทียบก่อนและหลังการใช้สติกเกอร์ป้าย การทดลองสติกเกอร์ป้ายครั้งนี้พบว่าได้ผลสำเร็จเป็นอย่างดี อปท. สามารถบริหารจัดเก็บภาษีป้ายภายในกำหนดเวลาในสัดส่วนที่เพิ่มขึ้น และเมื่อมีการแจ้งเตือนภาษีป้ายควบคู่ไปกับการใช้สติกเกอร์ป้ายก็พบว่า อปท. สามารถจัดเก็บภาษีป้ายได้ครบถ้วนในสัดส่วนที่สูงขึ้นอย่างมีนัยสำคัญ มาตรการดังกล่าวจึงสามารถนำไปขยายผลใน อปท. แห่งอื่น และสะท้อนถึงความสำคัญของการศึกษาวิจัยด้านพฤติกรรมศาสตร์สำหรับการบริหารงานคลังท้องถิ่นไทยต่อไปในอนาคต ABSTRACT This article explores the use and success in applying nudge approach to the collection of signboard tax in 2020. Four local administrative organizations are studied as an experimental group with one local administrative organization as a control group. Before-and-after comparison in tax collection outcomes is a major analytical technique in this study. Findings show that signboard stickers help to increase the effectiveness of signboard taxes significantly for all four local administrative organizations in the experimental group, comparing to the tax collection outcomes in the control group. This research sheds the light on the significance of behavioral studies for local tax administration in particular and for Thai public administration in general. Therefore, the measure shall be promoted in a wider scale.